Compressive properties on the spherical-roof contoured-core with different amounts of diamond-shaped notches - Quanjin, Ma; M. R. M., Rejab; M. S., Idris; Mohamad Nazirul Mubin, Merzuki; Shaoliang, Huang (2019)
It is a challenging task to develop lightweight materials and novel structures, which offers the better energy-absorbing characteristics. Therefore, it is still a significant issue to obtain secondary processing on available contoured-cores to provide a lightweight structure. This paper is aimed to investigate the effect of compressive properties on the single spherical-roof contoured-core cell with series diamond-shaped notches subjected to quasi-static compressive loading, which is referential concept on second weight reduction. The spherical-roof contoured-core panel was manufactured using the compression moulding process using carbon fibre reinforced laminates, and then cut to every single cell structure with 50×50 mm. The diamond-shaped notch is cut using hand saw with 1 mm thickness followed notch mould. It is concluded that with the number of diamond-shaped notches increasing, compressive strength and modulus generally shows the decreasing trend. Energy absorption, specific energy absorption and peak load are also studied. In addition, the failure types of single cell unit are discussed according to corresponding experimental results. It is highlighted that secondary process such as notch cutting process is a sufficient method to reduce weight reduction parameter of lightweight structure for automotive and aerospace application.